SWOT methodology: a state-of-the-art review for the past, a framework for the future - Ghazinoory, Sepehr; Abdi, Mansoureh; Azadegan-Mehr, Mandana (Journal of Business Economics and Management, 2011)
The SWOT analysis is the process of exploring the internal and external environments of an organization and extracting convenient strategies based on its strengths, weaknesses, opportunities and threats. This paper presents a literature review of SWOT analysis, based on a reference bank of about 557 papers established through searching various databases. This paper reviews papers that have been published up to the end of 2009. The origination and historical development of SWOT are explained first, followed by a survey on trends & classifications in SWOT papers including journals, countries, years, people & contents. Then a categorical analysis is conducted about application area and scope of SWOT. Also a methodological development of SWOT is discussed. Finally, concluding remarks and a few suggestions and challenges are presented for future studies. It is hoped that the paper can serve the needs of researchers and practitioners for easy references of SWOT studies and applications, and hence promote SWOT future development. Article in English. SSGG metodologija: praeities ir ateities analizė Santrauka. Straipsnyje nagrinejama SSGG metodologijos samprata, apibudinama kaip vidines ir išorines aplinkos tyrimas, pagristas silpnybiu, stiprybiu, galimybiu ir gresmiu identifikavimu. Pateiktoji SSGG analizes literaturos apžvalga yra pagrista 557 straipsniu, pateiktu ivairiose duomenu bazese, analize. Visi nagrineti straipsniai buvo publikuoti 2009 m. Pristatoma SSGG istorine raida, aiškinami tyrimai ir kryptys, klasifikacija, žurnalai, kuriuose publikuojami tokio pobudžio straipsniai, šalys, metai, autoriai, kontekstas, pritaikomumas ir ju sritys. Analizuojama SSGG metodologine raida. Straipsnio pabaigoje pateikiamos išvados ir busimu tyrimu gaires. Reikšminiai žodžiai: SSGG, žurnalu apžvalga, praeitis, strateginis planavimas, strategija.